2019
DOI: 10.1177/0748730419841185
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Clock Gene period in the Circadian Rhythm of the Silkmoth Bombyx mori

Abstract: In Lepidoptera, the roles of period ( per) and the negative feedback involving this gene in circadian rhythm are controversial. In the present study, we established a per knockout strain using TALEN in Bombyx mori, and compared eclosion and hatching rhythms between the per-knockout and wild-type strains to examine whether per is actually involved in these rhythms. The generated per knockout allele was considered null, because it encoded an extensively truncated form of PERIOD (198 aa due to a 64-bp deletion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…In turn, there was the activation and interaction between PER and TIM proteins with the CLK/CYC complex to suppress their own transcription (Rutila et al, 1998;Yu et al, 2006). The transcription levels of per in the control group had synchronized rhythms during the same phase, and consequently, peaked during the daytime as reported by Ikeda et al (2019) and Tao et al (2017). However, in our study, tim showed an antiphase rhythm in the control group, with a peak early during the night.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In turn, there was the activation and interaction between PER and TIM proteins with the CLK/CYC complex to suppress their own transcription (Rutila et al, 1998;Yu et al, 2006). The transcription levels of per in the control group had synchronized rhythms during the same phase, and consequently, peaked during the daytime as reported by Ikeda et al (2019) and Tao et al (2017). However, in our study, tim showed an antiphase rhythm in the control group, with a peak early during the night.…”
Section: Discussionsupporting
confidence: 48%
“…In this study, using the flexible genetic manipulation tool, the CRISPR/Cas9 system, we established the first tim ‐knockout strains of B. mori and revealed that tim was important in regulating the circadian rhythms at both phenotypic and genetic levels. Knockouts of three other genes have successfully been conducted in B. mori , including per (Ikeda et al ., 2019), and in D. plexippus , including clk and cry2 (Merlin et al ., 2013; Markert et al ., 2016). They revealed that circadian behavioral activities (hatching and eclosion) were inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…For the most part, masking has received attention in study of locomotor activity rhythm (Fry, 1947; Hamblen-Coyle et al, 1992; Kempinger et al, 2009; Rieger et al, 2003; Prabhakaran and Sheeba, 2012), although recently it has been invoked to explain aspects of eclosion rhythm in Drosophila (McNabb and Truman, 2008; Thakurdas et al, 2009) and the silk moth Bombyx mori (Ikeda et al, 2019). It is known that the lights-ON signal mediated masking of Drosophila eclosion rhythm is brought about by the release of eclosion hormone as removal of eclosion hormone neurons attenuates the masking response (McNabb and Truman, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For the most part, masking has received attention in study of locomotor activity rhythm (Fry, 1947; Sheeba et al, 2002), although recently it has been invoked to explain aspects of eclosion rhythm in Drosophila (McNabb and Truman, 2008; Thakurdas et al, 2009) and the silk moth Bombyx mori (Ikeda et al, 2019). It is known that the lights-ON signal mediated masking of Drosophila eclosion rhythm is brought about by the release of eclosion hormone (EH) as removal of EH neurons attenuates the masking response (McNabb and Truman, 2008).…”
Section: Discussionmentioning
confidence: 99%